Structural evolution during the graphitization of polyacrylonitrile‐based carbon fiber as revealed by small‐angle X‐ray scattering. (1st December 2014) - Li, Denghua; Lu, Chunxiang; Wu, Gangping; Hao, Junjie; Yang, Yu; Feng, Zhihai; Li, Xiutao; An, Feng; Zhang, Baoping
<x xml:space="preserve">Abstract</x> On the basis of a Debye–Bueche correlation length analysis, the small‐angle X‐ray scattering (SAXS) intensity components due to different scatterers within polyacrylonitrile‐based carbon fiber were determined and analyzed separately. According to Guinier's law and other related methods, an intensity component indicating a relatively large scatterer was ascribed to the amorphous structure within the boundaries of fibrils. Results indicated that the amorphous regions decreased in dimension and finally transformed completely into voids as the heat treatment temperature rose to 2773 K. The general trend for microvoids was a systematic change from many small voids to a few large voids, while the local density fluctuation within the samples weakened and finally faded away. In conclusion, the graphitization process of carbon fibers as revealed by SAXS is a systematic evolution from a quasi‐two‐phase system (fibril, amorphous region and microvoid within the fibril) of high‐strength carbon fiber to the true two‐phase structure (crystallite and microvoid) of high‐modulus graphite fiber.